2022
DOI: 10.1145/3495222
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the “Pathway” Towards a Searcher’s Learning Objective

Abstract: Search systems are often used to support learning-oriented goals. This trend has given rise to the “search-as-learning” movement, which proposes that search systems should be designed to support learning. To this end, an important research question is: How does a searcher’s type of learning objective (LO) influence their trajectory (or pathway ) toward that objective? We report on a lab study (N = 36) in which participants gathered information to meet a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In their study about search tactics in solving how‐to technical tasks, Rutter et al (2019) found that participants were able to find procedural information that was relevant but not necessarily useful in solving the task. Furthermore, Urgo and Arguello (2022) discovered that performing search tasks with procedural objectives required more creating compared to factual and conceptual objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study about search tactics in solving how‐to technical tasks, Rutter et al (2019) found that participants were able to find procedural information that was relevant but not necessarily useful in solving the task. Furthermore, Urgo and Arguello (2022) discovered that performing search tasks with procedural objectives required more creating compared to factual and conceptual objectives.…”
Section: Literature Reviewmentioning
confidence: 99%